Vibration and Performance Analyses Using Individual Blade Pitch Controls for Lift-Offset Rotors. (5th May 2019) - Park, Jae-Sang; Kim, Do-Hyung; Chae, Sanghyun; Lee, Ye-Lin; Go, Jeong-In
Abstract : This work attempts to reduce the hub vibratory loads of a lift-offset rotor using IBC (individual blade pitch control) in high-speed forward flight. As a lift-offset rotor for the present study, the rigid coaxial rotor of a XH-59A compound helicopter is considered and CAMRAD II is used to predict the hub vibration and rotor performance. Using the IBC with a single harmonic input at 200 knots, the vibration index of the XH-59A rotor is minimized by about 62% when the 3/rev actuation frequency is applied with the IBC amplitude of 1° and control phase angle of 270° (3 P /1°/270°); however, the rotor effective lift-to-drag ratio decreases by 3.43%. When the 2/rev actuation frequency with the amplitude of 2° and control phase angle of 270° (2 P /2°/270°) and the 3/rev actuation frequency using the magnitude of 1° and control phase angle of 210° (3 P /1°/210°) are used in combination for the IBC with multiple harmonic inputs, the vibration index is reduced by about 62%, while the rotor effective lift-to-drag ratio increases by 0.37% at a flight speed of 200 knots. This study shows that the hub vibration of the lift-offset rotor in high-speed flight can be reduced significantly but the rotor performance increases slightly, using the IBC with multiple harmonic inputs.